Public Values Leadership Striving to Achieve Democratic Ideals - Bozeman, Barry (Johns Hopkins University Press, 2021)
Instead of private gain or corporate profits, what if we set public values as the goal of leadership?Leadership means many things and takes many forms. But most studies of the topic give little attention to why people lead or to where they are leading us. In Public Values Leadership, Barry Bozeman and Michael M. Crow explore leadership that serves public values-that is to say, values that are focused on the collective good and fundamental rights rather than profit, organizational benefit, or personal gain. While nearly everyone agrees on core public values, there is less agreement on how to obtain them, especially during this era of increased social and political fragmentation. How does public values leadership differ from other types of organizational leadership, and what distinctive skills does it require? Drawing on their extensive experience as higher education leaders, Bozeman and Crow wrestle with the question of how to best attain universally agreed-upon public values like freedom, opportunity, health, and security. They present conversations and interviews with ten well-known leaders-people who have achieved public values objectives and who are willing to discuss their leadership styles in detail. They also offer a series of in-depth case studies of public values leadership and accomplishment. Public values leadership can only succeed if it includes a commitment to pragmatism, a deep skepticism about government versus market stereotypes, and a genuine belief in the fundamental importance of partnerships and alliances. Arguing for a "mutable leadership," they suggest that different people are leaders at different times and that ideas about natural leaders or all-purpose leaders are off the mark. Motivating readers, including students of public policy administration and practitioners in public and nonprofit organizations, to think systematically about their own values and how these can be translated into effective leadership, Public Values Leadership is highly personal and persuasive.